Effects of carbohydrate and caffeine-based energy gel ingestion on blood glucose, blood lactate and performance during prolonged cycling - Ulusoy, Y.; Kocak, F. (International Journal of Disabilities Sports and Health Sciences, 2023)
The aim of this study was to investigate the effects of carbohydrate and caffeine-based energy gels on blood glucose, blood lactate, heart rate, rating of perceived exertion (RPE), power output, cadence during prolonged cycling exercise. This research was an experimental study in which 15 competitor cyclists were tested in 3 different conditions. 3 experimental trials in a randomized order, no gel intake and water only use (T1), gel intake every 30 minutes (T2), 1 gel intake 15 minutes before exercise, and gel intake every 45 minutes after first gel intake and 1 carbohydrate + caffeine gel at 75 min (T3). Water use was released within 3 trials. Each exercise trial included 2 hours of cycling followed by 15 min TT. Measurements were made at the beginning, every 30 min, and at the end of the exercise. This research found that energy gels increased blood glucose levels and time trial (TT) performance compared to trials without consuming something. A more frequent gel intake improved blood glucose levels and TT distance. In the TT, blood lactate concentration increased significantly in T3 compared to T1 (p<0.05). Heart rate and RPE did not make a statistical difference (p>0.05). Even though cadence, power output, and TT distance in T3 were not statistically significant, the differences that occur are important in terms of cycling. The research also found no correlation between energy gel feedings and water intake (p>0.05). The results were important for cyclists with the positive effect on endurance performance when energy gels are used in long-term cycling exercises.